Glove-Induced Hand Dermatitis: A Study in Healthcare Workers during COVID-19 Pandemic in Indonesia - Cita Rosita Sigit Prakoeswa; null Damayanti; Sylvia Anggraeni; Menul Ayu Umborowati; Fajar Waskito; Niken Indrastuti; Sri Awalia Febriana; Agnes Rosarina Prita Sari; Kristo Alberto Nababan; Cut Putri Hazlianda; null Nopriyati; Windy Keumala Budianti; et al. (Hindawi Limited, 2023)
Skin damage among healthcare workers has been reported by many centers around the world. Occupational hand dermatitis is one of the most commonly known occupational skin diseases and a socially significant health issue. The use of gloves is one of the risk factors for the occurrence and/or aggravation of hand dermatitis. This cross-sectional study involved healthcare workers in 14 referral hospitals for COVID-19 throughout Indonesia. Questionnaires were distributed to the participants, which consisted of the subject's characteristics, glove-related skin problems, history of glove use, and clinical history. This study involved a total of 845 healthcare workers. Approximately 156 healthcare workers (18.46%) had glove-induced hand dermatitis during the pandemic. Itchy skin was the most common symptom (44.23%), and the palm was the most frequently complained area (48.72%). There was a significant association between glove use and glove-induced hand dermatitis among healthcare workers. In particular, equal to or more than 2 hours per day of glove use was significantly associated with hand dermatitis. Glove-induced hand dermatitis also had a significant association with the subject's history of atopic dermatitis and previous history of hand dermatitis. The use of gloves by healthcare workers should be considered carefully, especially in individuals at increased risk, including those who use gloves for 2 hours or more per day and those who have a history of atopic or hand dermatitis, in order to prevent the incidence of glove-induced hand dermatitis among healthcare workers, as well as to provide a safe working environment.